Association of prehospital post-resuscitation peripheral oxygen saturation with survival following out-of-hospital cardiac arrest. (December 2022) - Smida, Tanner; Menegazzi, James J.; Crowe, Remle P.; Bardes, James; Scheidler, James F.; Salcido, David D.
Abstract: Background: Hypoxia and hyperoxia following resuscitation from out-of-hospital cardiac arrest (OHCA) may cause harm by exacerbating secondary brain injury. Our objective was to retrospectively examine the association of prehospital post-ROSC hypoxia and hyperoxia with the primary outcome of survival to discharge home. Methods: We utilized the 2019–2021 ESO Data Collaborative public use research datasets for this study (ESO, Austin, TX). Average prehospital SpO2, lowest recorded prehospital SpO2, and hypoxia dose were calculated for each patient. The association of these measures with survival was explored using multivariable logistic regression. We also evaluated the association of American Heart Association (AHA) and European Resuscitation Council (ERC) recommended post-ROSC SpO2 target ranges with outcome. Results: After application of exclusion criteria, 19, 023 patients were included in this study. Of these, 52.3% experienced at least one episode of post-ROSC hypoxia (lowest SpO2  < 90%) and 19.6% experienced hyperoxia (average SpO2  > 98%). In comparison to normoxic patients, patients who were hypoxic on average (AHA aOR: 0.31 [0.25, 0.38]; ERC aOR: 0.34 [0.28, 0.42]) and patients who had a hypoxic lowest recorded SpO2 (AHA aOR: 0.48 [0.39, 0.59]; ERC aOR: 0.52 [0.42, 0.64]) had lower adjusted odds of survival. Patients who had a hyperoxic average SpO2 (AHA aOR: 0.75 [0.59, 0.96]; ERC aOR: 0.68 [0.53, 0.88]) and patients who had a hyperoxic lowest recorded SpO2 (AHA aOR: 0.66 [0.48, 0.92]; ERC aOR: 0.65 [0.46, 0.92]) also had lower adjusted odds of survival. Conclusion: Prehospital post-ROSC hypoxia and hyperoxia were associated with worse outcomes in this dataset.